The Egg: Memory and Visual Structures Within Representations of an Iconic Lebanese Ruin - Khoury, Melissa Plourde (2017)
he Egg is an iconic ruin in Beirut. It was once the Beirut City Centre's cinema, designed by Lebanese modernist architect Joseph Philippe Karam in 1965. This structure's use is complex and ever changing. As such, the Egg is a continuous source of discussions and depictions. This article is a textual analysis exploring visual structures within a series of 15 images of the Egg. The notion of memory is examined within each image. Memory is viewed as a phenomenon rooted in the past with a relationship to the present and the future. Contemporary representations of the Egg are a fascinating reflection related to Lebanon, the civil war, memories of today, and inquiries regarding the memories of unknown future contexts.